Foresight in Malaysia: a case study / Mohamad Hafiz Khairuddin - Khairuddin, Mohamad Hafiz (2013)
Foresight is a systematic, participative process which aims to acquire intelligence on the future based on medium term and long term visions which will assist the presentday decision making process in a collaborative effort. It can also assist the policy making process which in turn shapes the science, technology and innovation on various organizational levels. Since its rapid emergence in the 90s, Malaysia has also involved in such practices. However, little is known about Malaysia’s foresight initiative. The foresight initiative conducted by Malaysia since its involvement in 1997 until Malaysia’s first technology foresight initiative at the national level does not clearly show Malaysia’s position of its foresight initiative. The details of it and the way it is utilized are unknown at this point. This research aims to address this by providing a case study of foresight in Malaysia.